Diskresi Dalam Pelaksanaan Program Bantuan Siswa Miskin Sekolah Dasar di SDN Sebanen II Kalisat Kabupaten Jember - Altatur, Aulia Kamal; S, Supranoto; Makmur, M.Hadi (e-Sospol, 2015)
Abstract This research aimed to describe the implementation process of Bantuan Siswa Miskin (Cash Transfer for Poor Students) Program at Elementary School (BSM-SD) at SDN Sebanen II in Kalisat Jember using discretion in the program implementation. This is a descriptive research with qualitative approach. Data collection techniques used were observation, interview, documentation. Method of data analysis used Miles and Huberman interactive analysis consisting of three activity flows, namely data reduction, data presentation and conclusion withdrawing. Techniques of data validity applied triangulation. Based on the phenomenon occurred, the form of discretion in implementing BSM-SD program was discretion in social planning. Socio-economic condition of local community members and conflict potentials caused by jealousy became consideration implementing the program to reduce or adjust the provisions in the implementation of BSM-SD program.